The Effect of a Deproteinizing Pretreatment on the Bonding Performance and Acid Resistance of a Two-step Self-etch Adhesive on Eroded Dentin - Yang, Y; Inoue, G; Hosaka, K; Tichy, A; Ikeda, M; Tagami, J; Shimada, Y (Operative dentistry, 2024)
OBJECTIVES: This study evaluated how deproteinization using sodium hypochlorite (6% NaOCl) or hypochlorous acid (50 ppm HOCl) with or without the subsequent use of an arylsulfinate salt-containing agent (Clearfil DC Activator; DCA; Kuraray Noritake Dental) affects the micro-tensile bond strength (μTBS) and formation of an acid-base resistant zone (ABRZ) of a two-step self-etch adhesive on eroded dentin. METHODS: Coronal dentin surfaces of sound human molars were exposed to 48 cycles of demineralization (1% citric acid; 5 minutes) and remineralization (buffer solution with pH=6.4; 3.5 hours). They were then assigned to experimental groups according to the pretreatment used: none (negative control), NaOCl, NaOCl+DCA, HOCl, and HOCl+DCA. Sound dentin surfaces with no pretreatment were used as a positive control. The dentin surfaces were bonded with Clearfil SE Bond 2 (Kuraray Noritake Dental), and μTBS was measured either after 24 hours or 20,000 thermal cycles (TC). The μTBS data were statistically analyzed using a mixed-model analysis of variance (ANOVA) and t-tests with Bonferroni correction. Failure mode was determined with scanning electron microscopy (SEM), which was also used for the observation of ABRZ. RESULTS: Among experimental groups, there was no significant difference between the negative control, HOCl, and HOCl+DCA after 24 hours, but the HOCl-pretreated groups exhibited significantly higher μTBS than the negative control after TC (p<0.01). Pretreatment with NaOCl and NaOCl+DCA resulted in significantly higher μTBS (p<0.001), but the highest μTBS was measured on sound dentin (p<0.001). TC decreased μTBS significantly in all groups (p<0.001) except for sound dentin and NaOCl+DCA (p>0.05). Adhesive failures prevailed in eroded groups, whereas cohesive failures were predominant on sound dentin. ABRZ was recognized in all groups but marked morphological differences were observed. CONCLUSIONS: The combined use of 6% NaOCl and the arylsulfinate salt-containing agent partially reversed the compromised bonding performance on eroded dentin, while the effect of 50 ppm HOCl was negligible.
Keywords: testování materiálů; dentinová adheziva; pevnost v tahu; Materials Testing; Dental Cements; Resin Cements; zubní cementy; Humans; Dental Bonding; lidé; Tensile Strength; Dentin; pryskyřičné cementy; vazba zubní; Dentin-Bonding Agents; dentin